The Influence of Taxpayer Awareness and Tax Sanctions on Msme Taxpayer Compliance at Kpp Pratama Purwakarta District - Elyssa Fiqri Fauziah; Radhi Abdul Halim (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This research is motivated by the low level of taxpayer compliance as seen from the increase in the number of MSME taxpayers but not supported by fulfilling obligations to pay taxes, this is influenced by low awareness of taxpayers and tax sanctions. This study aims to determine whether the advice of taxpayers and tax sanctions affect taxpayer compliance of Micro, Small and Medium Enterprises (MSMEs) in Purwakarta Regency. The factors tested in this study suggest that taxpayers and tax sanctions are the independent variables, while taxpayer compliance is the dependent variable. The research method used is the verification method. The population in this study is MSMEs taxpayers who are registered at KPP Pratama Purwakarta Regency, totaling 1,608 MSMEs. The sampling technique used is the convenience sampling technique using the Slovin formula, so that the total sample is 100 MSMEs. The analytical method used is multiple linear regression analysis using the SPSS program. The results showed that the advice of taxpayers and tax sanctions had an effect on the compliance of the MSMEs taxpayers in Purwakarta Regency. In addition, the test results show that the influence of taxpayer advice and tax sanctions on MSME taxpayer compliance is 94.3%